Prevalence of Gastrointestinal Helminthes and Protozoa among Stray Dogs in Baghdad: Afkar M. Hadi1 and Azhar A. Faraj2 - Hadi, Afkar M. (The Iraqi Journal of Veterinary Medicine, 2016)
The aim of this study is to identify the gastrointestinal parasites and Protozoa in stray dogs. The current study include seven genera of intestinal helminthes and protozoa as follows: one cestode (Taenia sp. 29.1%), four nematode (Hookworm 86.6%, Toxocara canis 67.5%, Trichuris vulpis 51.6% and Stongyloides sp. 5%) and two protozoa (Gairdia sp. 24.1% and Cryptosporidium sp. 20.8%) from 120 fecal samples of dogs were collected from different regions of Baghdad during the period from February to July 2014.The results revealed that the intestinal parasites appeared in all months of study; however, the high rates of infection was during winter months.